Implementation of Green Human Resources Strategy (Study on Kampung Kue Rungkut) Based on SWOT - Rina Maretasari; Madziatul Churiyah (Dinasti International Journal of Education Management And Social Science, 2024)
To identify the internal and external environment with SWOT analysis in UMKM Kampung Kue Rungkut and formulate alternative business development strategies. The research method applied in this study is a qualitative descriptive approach. Data collection was done through observation, interview, and documentation. SWOT analysis indicates that Kampung Kue Rungkut has superior strengths and opportunities compared to the existing weaknesses and threats. Therefore, the direction of the business strategy being developed by these MSMEs supports the Aggressive Strategy. This research contributes to business development by explaining the green human resources strategy that MSMEs must implement to maximize opportunities and reduce threats.